2005
DOI: 10.1016/j.neurobiolaging.2004.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Event-related potentials accompanying motor preparation and stimulus expectancy in the young, young-old and oldest-old

Abstract: Although aging is accompanied by neurobiological changes and increased susceptibility to many neurological disorders, little is known about neurophysiological changes that start in old age. Here, neurophysiological changes during old age were assessed by recording brain potentials associated with motor preparation and stimulus expectancy (contingent negative variation, CNV) in young-old (60-69), oldest-old (85-98), and young (17-23) subjects. Individual trials began by a button press, followed 2.5 s later by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 65 publications
3
24
1
Order By: Relevance
“…The onset of the MRCPs in older adults was much earlier than previously reported in aging studies (Barrett et al, 1986;Falkenstein et al, 2006;Golob et al, 2005;Ishizuka et al, 1996;Kolev et al, 2006;Naccarato et al, 2006;Singh et al, 1990;Yordanova et al, 2004). Further, we found a large prefrontal involvement that has not been shown by earlier MRCP studies.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The onset of the MRCPs in older adults was much earlier than previously reported in aging studies (Barrett et al, 1986;Falkenstein et al, 2006;Golob et al, 2005;Ishizuka et al, 1996;Kolev et al, 2006;Naccarato et al, 2006;Singh et al, 1990;Yordanova et al, 2004). Further, we found a large prefrontal involvement that has not been shown by earlier MRCP studies.…”
Section: Discussionsupporting
confidence: 53%
“…The few and not very recent ERP studies comparing the cortical activity involved in motor planning by means of movement-related cortical potentials (MRCPs) in young and elderly subjects yielded inconsistent results. Indeed, MRCPs preceding voluntary movements in the elderly, as compared to the MRCPs of younger individuals, have been reported to be smaller in amplitude (Barrett et al, 1986), longer in latency (Ishizuka et al, 1996), or not different (Golob et al, 2005;Singh et al, 1990). More recent findings showed that the age-related RT slowing in sensorimotor tasks might originate at the motor response generation stage (about 400 ms before the response) and be attributable to a putative reduction in interhemispheric inhibition between the motor cortices via the corpus callosum Naccarato et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have reported somewhat smaller CNV amplitudes for older subjects (Loveless and Stanford, 1974;Michalewski et al, 1980). Recent findings indicate that substantial modulations in CNV amplitudes are observed in the oldest -old (Golob et al, 2004). Both groups had larger CNV amplitudes in the motor condition relative to the non-motor condition suggesting that CNV amplitude increases associated with motor preparation do not change with age.…”
Section: Potentials Between Cues and Targetsmentioning
confidence: 73%
“…Age-related slowing of RT, particularly during more complex RT conditions, is well documented (Jordan and Rabbitt 1977;Salthouse 2000) but, to date, the neural correlates of this phenomenon are not fully understood. Recent EEG studies have already indicated that information processing related to anticipation and preparation of a motor response changes during healthy aging (Golob et al 2005;Sterr and Dean 2008). Even though evidence suggests that older adults need stronger (amplitude enhancement) and longer (prolongation of the motor-related potential) activation of the contralateral motor cortex to trigger motor responses (Falkenstein et al 2006;Yordanova et al 2004), it still remains unclear whether these observations reflect deficits in movement preparation or response-generation processes or both.…”
Section: Discussionmentioning
confidence: 99%
“…Recent EEG studies have shown that brain activity related to anticipation, preparation, and/or generation of motor responses is changed in healthy aging (Falkenstein et al 2006;Golob et al 2005;Roggeveen et al 2007;Sailer et al 2000;Sterr and Dean 2008;Yordanova et al 2004). More specifically, Sterr and Dean (2008) showed that increased negativity of contingent negative variations (CNVs) in younger individuals during the preparatory period of a precued choice reaction time (CRT) task was associated with higher recruitment of the frontal brain network and lateralized activation over motor regions, whereas these trends were not seen in older individuals.…”
mentioning
confidence: 99%